Audit Operasional terhadap Pengelolaan Persediaan Obat dan Bahan Medis Habis Pakai - Nuri Aisyah Hikmah; Iyeh Supriatna (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This research aims to evaluate the activities of inventory drugs and consumable medical materials management in the Pharmacy Room UPTD Puskesmas Kasomalang, through the implementation of operational audits by empirically assessing the level of efficiency, effectiveness, and economy refers to Peraturan Menteri Kesehatan No.74 Tahun 2016. This study uses qualitative descriptive comparative method with the type of case studies which describe the conditions, criteria, causes, effects, and also strength-weakness matrix as an additional support data. This research uses qualitative data through triangulation procedures. The results show that the inventory of the drugs and consumable medical materials management in the pharmacy room in UPTD puskesmas kasomalang rates 85% for the effectiveness, 81.25% efficient, and 90.9% economical. But it still has some weaknesses, such as the existence of multiple positions, the occurrence of stockouts and stagnation, and also the administrative activities which are not fully computerized yet.